Implementation Of The Index Card Match Method In Learning Fiqh - Ahmad Husain; Zaenal Abidin (At-Tarbiyat, 2023)
The index card match method is a method that uses cards containing questions and answers by looking for pairs of cards, this method also creates fun and active learning so as to make students enthusiastic in the learning process. The index card match method has been applied in grade VII A of SMP Muhammadiyah Special Program KottaBarat Surakarta, this study aims to determine the implementation of the index card match method on student activity. The method used is descriptive qualitative, with the object of research being the implementation of the index card match method on student activity, the beautiful material of cultural diversity of my country and the subject of research, namely homeroom teachers and students of Class VII A. Data collection techniques use observation, interviews, and documentation. The results of this study show that the implementation of the index card match method on student activity of the beautiful material of cultural diversity of my country in VII A SMP Muhammadiyah Special Program KottaBarat Surakarta has 3 stages, namely 1) Planning stage, teachers make learning tools referring to the 2013 curriculum. 2) The implementation stage, in accordance with the theory of the steps of the index card match method on student activity. 3) The evaluation stage is carried out to see student activeness in the Jurisprudence material, Before using the index card match method, student activeness was only a few students who were active, after using the index card match method, student activeness increased to all active children. This is evidenced by looking at the evaluation answers in the student jurisprudence package book, and almost all students have met 8 indicators of student activeness, And among the 8 indicators are: carrying out learning tasks, expressing opinions, asking, reading, discussing, paying attention, training self-ability, applying abilities.